Developing English Interactive Multimedia (IMM) for Primary School - Cipta, Nyoman Fajar Ananda (Universitas Pendidikan Ganesha, 2012)
This study aimed at developing English interactive multimedia (IMM) for sixth grade students of second semester in Singaraja. This study was a development study consisting of ten stages, namely: (1) need assessment, (2) instructional analysis, (3) learners and context analysis, (4) writing performance objectives, (5) developing assessment instruments, (6) developing design of English IMM, (7) developing English IMM, (8) product evaluation, (9) revision, and (10) the final Product. This study used experts’ judgement and limited field try-out as product evaluation. Six experts evaluated the product on three aspects (content, instruction and multimedia). The result showed the score of 3.96 (very good) within 0 – 4.00 scale. In limited field try-out, the subjects were the sixth graders of three elementary schools in Singaraja representing all accreditation grades (grade A, B and C). The result showed students’ responses trough post questionnaires: 68.02% of total responses indicated very good English IMM; and 30.08% indicated good English IMM. It means that the English IMM has been developed appropriately for both individual learning and classical instruction.